Proposed new interior design scheme of meteorology interactive gallery for Malaysian Meteorological Department at no.252 Jalan Tun Razak, 50400 Kuala Lumpur / Amy Fadzillah Ibrahim - Ibrahim, Amy Fadzillah (2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student's knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to Propose New Interior Design Scheme Of Meteorology Interactive Gallery For Malaysian Meteorological Department At no.252 Jalan Tun Razak, 50400 Kuala Lumpur. This Meteorology Interactive Gallery is being developed to stimulate interest in the scientific fields of meteorology and its instrument, to provide a facility for people of all ages to learn about the weather, obtain weather safety information, and to look into the past at how weather was observed. The Weather Museum is a project of Malaysia Meteorology Department.Too many lives are lost and too much property destroyed due to the lack of weather safety information reaching the public. This gallery will distribute weather safety information as well as maintain exhibits and programs that increase knowledge about weather. The Weather Museum is an innovative, interactive, educational facility that will continue to grow in service to the community. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Meteorology Interactive Gallery. Connected to that, the chosen design style for this project is based on modern and fun design, goes all the way with the client's needs as they want the gallery to attract more children to visit the first meteorology gallery in Malaysia. Before getting a desired design that is suitable with the client's needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services, spaces to be concluded in the proposed area, operation time and information about other gallery that use the same system in management. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.